Inducing half metallicity with alloying in Heusler Compound CoFeMnSb. (31st May 2019) - Kumar, Upendra; Sreenivasa Reddy, P V; Bhattacharjee, Satadeep; Lee, Seung-Cheol
Abstract: First principles studies were performed in order to find out the possibility of inducing half-metallicity in Heusler Compound CoFeMnSb, by means of alloying it with 3d-transition metal elements. Proper alloying element is selected through the calculations of formation energies. These calculations were tested with different concentrations of alloying elements at different atomic sites. Among the selected transition metal elements Sc and Ti are proposed to be excellent alloying elements, particularly at Mn site. By using these alloying elements complete half metallic behaviour is obtained in, , , , and CoFeTiSb alloys. Shifting of Co–Fe d-states towards lower energy region leads to zero density of states at Fermi level for the spin minority channel. Alloying effects on the electronic structure and magnetization are discussed in details. Thermodynamical stability of these new alloys is a major part of this study. The Curie temperatures of and were found to be 324.5 K and 682 K; respectively, showing good candidature for spintronics applications. For understanding the bonding nature of the constituent atom of CoFeMnSb, crystal orbital Hamiltonian populations have been analysed.